Kidney volume normative values in Central European children aged 0-19 years: a multicenter study - Obrycki, Łukasz; Sarnecki, Jędrzej; Pac, Michał; Lichosik, Marianna; Sopińska, Małgorzata; Placzyńska, Małgorzata; Milart, Joanna; Stańczyk, Małgorzata; Mirecka, Julia; Wasilewska, Agnieszka; Michalski, Maciej; Lewandowska, Weronika; et al. (Pediatric nephrology (Berlin, Germany), 2024)
BACKGROUND AND OBJECITVES: The currently available kidney volume normative values in children are restricted to small populations from single-centre studies not assessing kidney function and including none or only a small number of adolescents. This study aimed to obtain ultrasound-based kidney volume normative values derived from a large European White/Caucasian paediatric population with normal kidney function. METHODS: After recruitment of 1427 children aged 0-19 years, 1396 individuals with no history of kidney disease and normal estimated glomerular filtration rate were selected for the sonographic evaluation of kidney volume. Kidney volume was correlated with age, height, weight, body surface area and body mass index. Kidney volume curves and tables related to anthropometric parameters were generated using the LMS method. Kidney volume predictors were evaluated using multivariate regression analysis with collinearity checks. RESULTS: No clinically significant differences in kidney volume in relation to height were found between males and females, between supine and prone position and between left and right kidneys. Males had, however, larger age-related kidney volumes than females in most age categories. For the prediction of kidney volume, the highest coefficient correlation was observed for body surface area (r = 0.94), followed by weight (r = 0.92), height (r = 0.91), age (r = 0.91), and body mass index (r = 0.67; p < 0.001 for all). CONCLUSIONS: This study presents LMS-percentile curves and tables for kidney volume which can be used as reference values for children aged 0-19 years.
Keywords: Infant; ledviny; hodnoty glomerulární filtrace; tělesná hmotnost; ultrasonografie; index tělesné hmotnosti; předškolní dítě; Humans; Ultrasonography; Europe; mladý dospělý; Children; Body Mass Index; mužské pohlaví; Normal references; Organ Size; Age Factors; Child, Preschool; referenční hodnoty; Adolescent; Infant, Newborn; Evropa; novorozenec; Kidney volume; ženské pohlaví; věkové faktory; Kidney; velikost orgánu; lidé; mladiství; Body Weight; dítě; Child; Reference Values; Glomerular Filtration Rate; Male; Young Adult; kojenec; Female